2023
DOI: 10.1186/s12575-023-00190-6
|View full text |Cite|
|
Sign up to set email alerts
|

Isolation and characterization of apical papilla cells from root end of human third molar and their differentiation into cementoblast cells: an in vitro study

Abstract: Background Periodontal regeneration, treatment of periodontal-related diseases and improving the function of implants are global therapeutic challenges. The differentiation of human stem cells from apical papilla into cementoblasts may provide a strategy for periodontitis treatment. This study aimed to evaluate the differentiation of primary human stem cells apical papilla (hSCAPs) to cementoblast cells. Material and methods SCAPs cells were isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…It is demonstrated that SCAPs hold the capacity to regenerate dentin-like and pulp-like tissue in vivo ( Sonoyama et al, 2006 ; Huang et al, 2010 ; Hilkens et al, 2017 ). Besides, SCAPs can also differentiate into cementoblasts in vitro , which hold the promise for periodontal regeneration ( Ebadi et al, 2023 ).…”
Section: The Stem/progenitor Cells Used In the Dentistry 3d Printingmentioning
confidence: 99%
“…It is demonstrated that SCAPs hold the capacity to regenerate dentin-like and pulp-like tissue in vivo ( Sonoyama et al, 2006 ; Huang et al, 2010 ; Hilkens et al, 2017 ). Besides, SCAPs can also differentiate into cementoblasts in vitro , which hold the promise for periodontal regeneration ( Ebadi et al, 2023 ).…”
Section: The Stem/progenitor Cells Used In the Dentistry 3d Printingmentioning
confidence: 99%
“…As a subgroup of dental mesenchymal stem cells (MSCs), human stem cells from apical papilla (hSCAPs) can be obtained from the apical tissue of underdeveloped permanent teeth and have been identified as promising seed cells in tissue engineering due to their self-renewal and multi-lineage differentiation potential ( 5 7 ). Owing to the capacity to diverge into distinct cell lineages, such as odontogenic, neurogenic, chondrogenic and osteogenic, hSCAPs play a vital role in the development of the root, pulp-dentin complex, and alveolar bone ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the version of this article originally published [ 1 ], there was an error in the author's order. The order of authors is now corrected in the author group and the original article has been corrected.…”
mentioning
confidence: 99%